Service Quality Management in Public and Private Hospitals in Indonesia: Comparative Analysis Based on Law Number 17 of 2023 concerning Health - Septien Dwi Savandha (Fakultas Hukum Universitas Gresik, 2026)
Background: Despite the enactment of a unified regulatory framework under Law Number 17 of 2023, service management quality in Indonesian hospitals remains markedly unequal between public and private providers. This study empirically evaluates the administrative performance differential between the two sectors following the law’s implementation, with particular attention to governance constraints inherent in the Regional Public Service Agency (BLUD) model. Methods: A mixed-method design used a 50-item Likert survey (n=684) of administrators, staff, and patients across 30 public and 30 private hospitals in Java and Sumatra, alongside 24 semi-structured interviews and analysis of SPM, KARS, and CMKP documents. Quantitative data were integrated into the Service Management Quality Index (SAQI) using TOPSIS entropy, and comparisons were performed using t-tests and Mann-Whitney U tests. Results: Private hospitals rated public hospitals higher on six SAQI aspects (responsiveness, regulatory compliance, accountability, patient-centricity, human resource management, operational autonomy) and on the composite indices (public M=0.58, private M=0.74; d=1.95; p<.001). Documents show private hospitals improved SPM achievement, increased plenary KAS certification, and had fewer patient safety incidents. Law No. 17/2023 and Govt Regulation No. 28/2024 promote some convergence between mediation and complaint procedures but reveal ongoing structural constraints in BLUD governance within public hospitals. Conclusion: While legislative changes improved hospital service management, the public-private quality gap in Indonesia's dual hospital system remains. Without reforms to boost BLUD's autonomy, regulations under the Health Law 2023 could worsen management inequalities.